Prevalence of illness, poor mental health and sleep quality and low energy availability prior to the 2016 Summer Olympic Games. Issue 1 (22nd October 2017) - Drew, Michael; Vlahovich, Nicole; Hughes, David; Appaneal, Renee; Burke, Louise M; Lundy, Bronwen; Rogers, Margot; Toomey, Mary; Watts, David; Lovell, Gregory; Praet, Stephan; Halson, Shona L; et al.
Abstract : Objective: Establish the prevalence of illness symptoms, poor sleep quality, poor mental health symptoms, low energy availability and stress-recovery state in an Olympic cohort late in the 3 months prior to the Summer Olympic Games. Methods: Olympic athletes (n=317) from 11 sports were invited to complete questionnaires administered 3 months before the Rio 2016 Olympic Games. These questionnaires included the Depression, Anxiety and Stress Questionnaire, Perceived Stress Scale, Dispositional Resilience Scale, Recovery-Stress Questionnaire (REST-Q-52 item), Low Energy Availability in Females Questionnaire (LEAF-Q), Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index and custom-made questionnaires on probiotic usage and travel. Multiple illness (case) definitions were applied. ORs and attributable fractions in the population were used. Factor analyses were used to explore the relationships between variables. Results: The response rate was of 42% (male, n=47, age 25.8±4.1 years; female, n=85, age 24.3±3.9 years). Low energy availability was associated with sustaining an illness in the previous month (upper respiratory, OR=3.8, 95% CI 1.2 to 12). The main factor relating to illness pertained to a combination of anxiety and stress-recovery states (as measured by the REST-Q-52 item). All participants reported at least one episode of illness in the last month (100% prevalence). Conclusions: All participants reported at least one illness symptom in the previous month. Low energy availability was a leading variable associated with illness in Olympic-class athletes. The estimates duration of symptoms ranged from 2 to 7 days. Factor analyses show the interdependence of various health domains and support multidisciplinary care.